Gene expression of Anopheles dirus stat pathway in response to Plasmodium berghei infection / Jonathan Liew Wee Kent - Jonathan Liew, Wee Kent (2018)
The signal transducers and activators of transcription (STAT) pathway is one of the main signaling pathways mediating immune responses towards Plasmodium parasites in Anopheles. Core components of the STAT pathway are STAT, suppressor of cytokine signaling (SOCS) protein, and protein inhibitor of activated STAT (PIAS) protein. The pathway regulates expression of two potent anti-Plasmodial factors, the thioester-containing protein 1 (TEP1) and nitric oxide synthase (NOS). Recent study found that Anopheles dirus lacks a second intronless STAT (STAT-B). The implication of this phenomenon is still unclear. Moreover, molecular understanding of the immune response of An. dirus, a major Southeast Asian malaria vector, is scarce. Thus, the components of the pathway were studied using the An. dirus/P. berghei experimental model. Evaluation of the vector competence of An. dirus for P. berghei ANKA indicated that An. dirus was highly permissive to P. berghei. Infection intensity in the mosquito was dependent on the parasitemia and phase of infection in the mouse. Then, the STAT-A, PIAS and SOCS coding sequences were cloned and characterized. They exhibit high sequence similarities with those of other Anopheles. Gene expression levels of these genes, along with TEP1 and NOS, during P. berghei infection were then studied using quantitative reverse transcription PCR (qRT-PCR). However, most studies used a single reference gene for normalization in their gene expression analyses which may lead to erroneous results. In the current study, the elongation factor 1-alpha (EF1), actin 1 (Act) and ribosomal protein S7 (S7) genes were validated for their suitability as a set of reference genes prior to gene expression analysis. There were no significant changes in the expression levels of STAT-A, PIAS and SOCS post P. berghei infection. This finding is in contrast with results of other studies. This may be caused by the iv absence of STAT-B in An. dirus. Nonetheless, the NOS relative expression peaked at 48 h post infectious blood meal with a 1.91-fold increase, while that of TEP1 was upregulated 3-fold at 24 h post infection. RNA sequencing was also performed on An. dirus infected with P. berghei at 24 and 48 h post infection. Gene ontology (GO) annotation of the differentially expressed genes revealed GO terms enriched in protein and carbohydrate metabolism, peptidase activity and oxidoreductase activity. Analyses of the transcriptomes revealed only a handful of common immunity-related genes associated with the Imd pathway, TEP1 and JNK pathway to be differentially expressed. In conclusion, the current study established the An. dirus/P. berghei model which can facilitate further studies on An. dirus immune responses. It also elucidated details of the An. dirus STAT pathway and other immunity-related genes which could be potential targets for transmission blocking strategies in the mosquito. More functional assays and experiments should be done to confirm and understand the implication of the study. Molecular studies on primary malaria vector of Southeast Asia should also be pursued, to understand the possible differences among Anopheles of different geographical regions.